Pengaruh Kepemimpinan, Disiplin Kerja, dan Remunerasi Terhadap Semangat Kerja dan Implikasinya pada Kinerja - Ahmad Zaini; Gunistiyo; Dien Noviany Rahmatika (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of this study is to determine the influence of leadership on morale, the influence of work discipline on morale, the effect of remuneration on morale, the influence of leadership on employee performance, the influence of work discipline on employee performance, the effect of remuneration on employee performance, the influence of morale on employee performance, the significance of morale in mediating the influence of leadership on employee performance, significance morale in mediating the influence of work discipline on employee performance, the significance of morale in mediating the effect of remuneration on employee performance. The subjects of this study were employees of Perumda Air Minum Tirta Baribis Brebes Regency totaling 167 employees. The technique used to collect data in this research is a questionnaire. The data analysis methods used in this study are instrument validity and reliability tests, descriptive statistics, quantitative analysis, and mediation tests (sobel test). Some conclusions that can be drawn from this study are that leadership, work discipline, and remuneration affect morale. Leadership, work discipline, and remuneration affect employee performance. Morale is able to significantly mediate the influence of leadership, work discipline and remuneration on employee performance.